The Importance of Teaching English for Medical Purposes to Medical Doctors at Batna Hospital University Centre - Romane , Karima; Bahloul , Amel (مجلة العلوم الاجتماعية والانسانية, 2022)
To contribute to national and international scientific development, researchers need to acquire academic discourse community membership for the purposes of information exchange through conferences, published research articles and the like. Therefore, learning English appears to be essential for academic studies of graduate as well as postgraduate students, who need to pursue the world’s scientific and technological development. In Algeria, the increasing demand from the part of medical students and doctors to take private courses in English, due to lack of an English module at the department of Medicine in all the Algerian universities, leads us to think about the importance of English for Medical Purposes to medical students and doctors. In this paper, the intention is to be able to design a course that meets medical students and doctors’ needs, interests, and to attract the attention of decision makers and programme designers to the teaching of English for Medical Purposes. Based on a needs analysis approach, a questionnaire is addressed to medical doctors at Batna Hospital University Centre. It helped to identify the needs of medical doctors to learn the English language. The tool of research used here corroborate the hypotheses and answer the research questions; it indicates that the teaching of English for Medical Purposes would certainly result in beneficial results for the medical doctors.